Role of β2-microglobulin in postoperative cognitive decline. (March 2017) - Załęska-Kocięcka, Marta; Jezierski, Paweł; Grabowski, Maciej; Kuśmierski, Krzysztof; Dąbrowski, Maciej; Piotrowska, Katarzyna; Banaszewski, Marek; Imiela, Jacek; Stępińska, Janina
Aim: β2-microglobulin (β2M) was proved to affect hippocampal functions in mice.Materials & methods: Seventy-one patients undergoing aortic valve replacement were analyzed in prospective observational study. Kidney biomarkers and Mini Mental State Examinations (MMSEs) were performed before procedure, at discharge and after 6 months.Results: Patients with β2M increase over the median change (>0.42 mg/l) experienced a significant in-hospital drop in MMSE (p = 0.005). Patients with β2M increase over the median change also failed to improve a delayed-word-recall domain of the test (p = 0.826) while patients with a lower increase improved results in the domain (p = 0.004). After 6 months, MMSE improvement was associated with a significant decrease in β2M (p = 0.042).Conclusion: These are the first in man data demonstrating relation between changes in cognition and β2M. The phenomenon was reversible which indicates its therapeutic potential.